#### Answer

$0$

#### Work Step by Step

Using $i^2=-1$ and the laws of exponents, the given expression, $
i^2+i^4
,$ is equivalent to
\begin{array}{l}\require{cancel}
i^2+(i^2)^2
\\\\=
(-1)+(-1)^2
\\\\=
-1+1
\\\\=
0
\end{array}

Published by
Pearson

ISBN 10:
0-32184-874-8

ISBN 13:
978-0-32184-874-1

$0$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.